Community Theatre and Development Practices in the Nyanza Region of Kenya - Mwai, Wangari; Diang’a, Rachael; Kebaya, Charles (My University, 2015)
Positing Community Theatre as an agency for development and is an effective way to encourage community dialogue, this article interrogates practices and efficacies of Community Theatre in Nyanza, Kenya. While contending that it has the potential to build developmental consciousness among community members on social issues affecting them, the study argues that Community Theatre provides an interesting way to explore cultural, socio-economic and developmental realities, thereby changing the way people think, socialize and act. Based on selected Community Theatre performances in Nyanza, this article analyses the practice and efficacy of Community Theatre as a social construction that is produced, regulated and consumed within specific cultural frameworks. Anchored in qualitative research, participant observation and post-performance discussions were used in data collection. The data responses obtained were organized into thematic analysed and interpreted strands, and thus, the findings show that Community Theatre is a crucial space in communities that can increase social issue awareness, influence beliefs and attitudes, prompt action, increase utilization of and support for services, explore popular misconceptions, and strengthen community support for recommended practices. Hence, Community Theatre is a safe space where communities can explore difference, question everyday life, and say the unsayable.